Implementation of a modified obstetric early warning system to improve the quality of obstetric care in Zimbabwe. Issue 2 (21st November 2016) - Merriel, Abi; Murove, Bobb T.; Merriel, Samuel W.D.; Sibanda, Thabani; Moyo, Sikangezile; Crofts, Joanna
Abstract: Objective: To implement a modified obstetric early warning system (MOEWS) to promote identification and stabilization of unwell women. Methods: A before‐and‐after study of MOEWS implementation took place between April 2013 and January 2014 in a government referral hospital in Bulawayo, Zimbabwe. After piloting MOEWS, cesarean case files were retrospectively assessed to compare preoperative stabilization. A longitudinal "spot‐check" study measured use of MOEWS and action taken on abnormal results. A quality indicator was introduced to assess ongoing implementation. Results: Analysis of women undergoing cesarean before (n=79) and after (n=85) MOEWS implementation showed that preoperative stabilization improved significantly post‐intervention (odds ratio 2.78, 95% confidence interval 1.39–5.54). The longitudinal analysis of women at baseline (n=43) and after (n=85) MOEWS implementation also showed a significant improvement in action taken (1/24 [4%] vs 28/45 [62%]; P= 0.001). The 6‐month aggregated quality indicator revealed that 78 (62%) of 125 patients had a completed MOEWS chart, with appropriate stabilization of 65 (93%) of 70 women. Conclusion: Implementation of MOEWS improved women's care through action being taken on abnormal observations. Before whole‐scale adoption of MOEWS in low‐resource settings, the study should be scaled up and repeated to ensure replicable findings. Abstract : Implementation of a modified obstetric early warning system in Zimbabwe has improved action on abnormal observations. This simple system can empower staff and improve care.